(untitled) - Sharma, Vartika; Singh, Seema (Asian Journal of Medical Research, 2023)
Schwannomas or neurilemmomas are benign neoplasms arising from Schwann cells. They usually occur in the head and neck region or upper extremities but may also appear in any nerve in the body. Breast schwannomas are rare neoplasms; however, it is difficult to distinguish them clinically and radiologically from other mammary nodules. They might even simulate a malignant neoplasm. Our report summarises a case of a 52-year-old male with a 4-month history of a right-sided palpable breast mass. This clinical study demonstrates the importance of Intramammary schwannoma as a significant differentiator when evaluating a breast mass in diagnosing a breast tumour.